The Predicting Power of Cognitive Fluency for the Development of Utterance Fluency in Simultaneous Interpreting - Song, Shuxian; Li, Dechao (Frontiers in Psychology, 2020)
Although simultaneous interpreting (SI) is generally recognized as a high-demanding cognitive activity in nature, the role of cognitive processes in SI fluency is yet to be determined. While utterance fluency refers to the set of objectively determined oral features of utterances, cognitive fluency means the speaker’s efficient mobilization and integration of underlying cognitive processes responsible for utterance production. An investigation into the relationship of the two dimensions of fluency helps to reveal the cognitive bases of interpreting. This study explores the predicting power of cognitive fluency in the utterance fluency development of L2 (English)-L1 (Chinese) SI output of trainee interpreters. Cognitive fluency was operationalized as measures of lexical access, linguistic attention control and working memory capacity. Measures of utterance fluency were obtained through simulated SI tasks under conditions of low and high input rates. Twenty-eight trainees interpreted two speeches, one with a high input rate and the other with a low input rate, at the beginning and end of an SI training period of thirteen weeks. A bilingual corpus of the participants’ SI output was built, and indicators of SI utterance fluency were annotated systematically. Utterance fluency was indexed by the speech rate, mean length of run, phonation time ratio, mean number of silent pauses and mean number of disfluencies. Results of analyses indicated that (1) the predicting power of cognitive fluency for SI utterance fluency development was only shown under high cognitive load over a training period of thirteen weeks; (2) predictors for the development of SI utterance fluency tended to be the efficiency of cognitive processes involved in the target language production stage; (3) the inclusion of measures of working memory capacity significantly increased the predicting power of cognitive fluency for SI utterance fluency development. This study for the first time provides evidence for the role of cognitive fluency in trainee interpreters’ SI utterance fluency development, having implications for the theoretical framework of cognitive fluency and the information processing mechanism in interpreting process, as well as for interpreter aptitude tests and interpreting pedagogy.